Body language secrets to win more negotiations how to read any opponent and get what you want - Williams, Greg; Iyer, Pat (Career Press, 2016)
The success of a negotiation is profoundly affected by how well you read body language. How can you learn to read the subtle clues many lasting a fraction of a second that your opponent projects?
Includes index. - Description based on online resource; title from title page (Safari, viewed October 5, 2016)
Keywords: Negotiation in business; Body language; Nonverbal communication; Kinesics; Nonverbal Communication; Négociations (Affaires); Langage du corps; Communication non verbale